A Prototype Web-Based Emergency Response System That Incorporates the Findings from the Shortest Route Techniques for Path Optimization (International Journal of Innovative Research in Computer Science & Technology, 2020)
This paper holistically reviewed the present  emergency response operations of the Lagos State  Emergency Management Authority (LASEMA), and  identified deficiencies. This ultimately led to the  development of an improved network, premised on the  assumption that all the response management sub-stations  (LRU) of LASEMA in Lagos State were networked to a  central location where all command operations are easily  disseminated. An improved framework was then designed,  that utilised an improved Ant Colony Optimization technique layered on the Google Map functionality to  determine the shortest route to an incident site for the  emergency vehicle conveying the first responders to the  incident site. A detailed discussion on the design,  development, implementation and evaluation approaches  used for the Emergency Response Management System  (ERMS) was done. How data used in this work were  collected, tested for quality of its contents and then  analysed using the descriptive analysis of the Statistical  Package for Social Sciences (SPSS) software was  extensively discussed.  Also, the data collected before and after the implementation  of the developed Emergency Response Management  System (ERMS) were analysed using the descriptive  analysis of the SPSS software, as to measure the perceived  performance of the system, based on the variables defined  from the Technology Acceptance Model (TAM). From the  analyses of the results of these metrics, we concluded that  the ERMS was able
Keywords: Emergency Response Management System; Technology Acceptance Model; Ant Colony Optimization algorithm; Lagos State Emergency